2020
DOI: 10.1042/bsr20191900
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1/LINC00152 feedback loop regulates proliferation and apoptosis in rheumatoid arthritis fibroblast-like synoviocytes via Wnt/β-catenin signaling pathway

Abstract: Rheumatoid arthritis (RA), a chronic systemic disease, is featured with inflammatory synovitis, which can lead to destruction on bone and cartilage and even cause disability. Emerging studies demonstrated that Fibroblast-like synoviocytes (FLS) is a vital cellular participant in RA progression. Long non-coding RNAs (lncRNAs) are also reported to participate in the pathogenesis of RA. In our present study, lncRNA microarray analysis was applied to screen out lncRNAs differentially expressed in RA FLS. Among whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The previous studies have found that LINC00152 could compete as a ceRNA with miRs to fulfil its functions in hepatic and cervical cancers [11,15,30,31] . Besides, LINC00152 is related to the regulation of signaling pathways such as Wnt/β-Catenin pathway [12,32] . In contrast, Our MS/LS data based on RNA-pulldown assays and in vitro experiments suggested that oncogenic BCL6 was the posttranslational regulation target of LINC00152, and LINC00152 promoted ovarian tumor invasion and metastasis in a BCL6-mediated manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies have found that LINC00152 could compete as a ceRNA with miRs to fulfil its functions in hepatic and cervical cancers [11,15,30,31] . Besides, LINC00152 is related to the regulation of signaling pathways such as Wnt/β-Catenin pathway [12,32] . In contrast, Our MS/LS data based on RNA-pulldown assays and in vitro experiments suggested that oncogenic BCL6 was the posttranslational regulation target of LINC00152, and LINC00152 promoted ovarian tumor invasion and metastasis in a BCL6-mediated manner.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have got similar findings in gastric cancer [10] and hepatic carcinoma [11] , suggesting that LINC00152 might serve as a powerful oncogenic lncRNA in somatic malignancies. Researchers have found that LINC00152 forms the loop feedback with FOXM1 to stimulate tumor growth [12] and might serve as the ceRNA (competing endogenous RNA) to regulate miRNAs to fulfil its biological functions [5,13,14] . Although the impact of LINC00152 on ovarian cancer proliferation has been implicated recently [15] , its role and the exact molecular mechanism to regulate the ovarian tumor behavior need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FER1L4 regulates inflammation in RA FLSs by potentially targeting NLRC5 [ 79 ]. Several lncRNAs, including MALAT1 [ 80 ], UCA1 [ 81 ], DILC [ 82 ], LncIL7R [ 83 ] and LINC00152 [ 84 ], have been reported to contribute to apoptosis and proliferation in RA-FLSs. lncRNA GAS5 [ 85 , 86 ] and ITSN1-2 [ 87 ] are implicated in apoptosis and inflammation in RA FLSs.…”
Section: Important Roles Of Lncrnas In Autoimmune Diseasesmentioning
confidence: 99%
“… [ 80 ] UCA1 Human FLS Down-regulated Induces apoptosis by Wnt6 [ 81 ] DILC Human FLS, plasma Down-regulated Regulates apoptosis and IL-6 expression. [ 82 ] Lnc-IL7R Human FLS Promotes growth of RA FLS through interaction with EZH2 [ 83 ] LINC00152 Human FLS Up-regulated Regulates proliferation and apoptosis via Wnt/beta-catenin signaling pathway [ 84 ] GAS5 Human Tanshinone IIA -treated FLS, plasma Down-regulated Responsible for apoptosis and IL-18 expression. [ 85 , 86 ] ITSN1-2 Human FLS Up-regulated Regulates apoptosis, proliferation and inflammation by NOD2/RIP2 pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation